Psychotherapist Trainees’ Quality of Life: Patterns and Correlates - Heinonen, Erkki; Orlinsky, David E.; Willutzki, Ulrike; Rønnestad, Michael Helge; Schröder, Thomas; Messina, Irene; Löffler-Stastka, Henriette; Hartmann, Armin (Frontiers in Psychology, 2022)
While psychotherapists are trained to improve their clients’ quality of life, little work has examined the quality of life experienced by psychotherapist trainees themselves. Yet their life satisfactions and stresses would plausibly affect both their ability to learn new skills and conduct psychotherapy. Therefore, in the Society for Psychotherapy Research Interest Section on Psychotherapist Development and Training study, we investigated the patterns of self-reported life quality and their correlates in a multinational sample of 1,214 psychotherapist trainees. A comprehensive questionnaire was used at the outset of trainings to assess trainees’ professional background, current life situation, personal characteristics, family background, and social and national origin. The findings indicated 54.3% of trainees’ lives could be characterized as fortunate or happy (i.e., experiencing great life satisfaction and not much stress), whereas 14.3% could be characterized as clearly distressed or troubled (i.e., experiencing great life stress and not much satisfaction). The strongest correlates of high life stress, a contributor to poor life quality, were economic insecurity, self-protectiveness, and attachment-related anxiety in relationships, and economic or psychological hardship in childhood. In turn, greater wellbeing was most strongly associated with a warm and open interpersonal style, being married, having sufficient economic means, and material and emotional security in childhood. While the results indicate the majority of therapists experience a relatively good quality of life, the findings also suggest potential targets for increasing trainees’ life quality when it may be deficient, such as those on a societal level (e.g., availability of low-cost student loans), training program level (e.g., promoting supportive supervision, positive between-trainee relationships and group collaboration), and individual level (e.g., personal therapy and learning self-care), in order to promote effective learning and therapy practice.